The role of the social environment in the relationship between group-focused enmity towards social minorities and politically motivated crime = Die Rolle des sozialen Umfelds hinsichtlich des Zusammenhangs zwischen gruppenbezogener Menschenfeindlichkeit und politisch motivierter Kriminalität - Krieg, Yvonne (Kölner Zeitschrift für Soziologie und Sozialpsychologie, 2022)
Politically motivated crime against a person is characterised by the fact that the victims are interchangeable in the sense that individuals are seen as representatives of their social or ethnic group. The current study examines whether the existence of group-focused enmity (GFE) is linked to the perpetration of discriminatory behaviour, in the form of politically motivated crime, which is considered a classic example of the attitude–behaviour relationship. Although various survey studies show connections between group-focused enmity towards social minorities and discriminatory behavioural intentions, there is less knowledge available on whether attitudes can also be regarded as potential risk factors for actual behaviour. The role of the social environment in this relationship, as well as how the attitudes of the social environment are related to the perpetration of politically motivated crime, regardless of personal group-focused enmity, are further analysed. Using a representative student sample from the year 2018 (N= 2824), results show that anti-immigrant, anti-gay, ableist and anti-homeless attitudes are potential risk factors for the perpetration of politically motivated crime against these social minority groups, even after controlling for various other correlates of politically motivated crime. Group-focused enmity has an even greater effect when the student has a like-minded friendship group. Moreover, if the adolescent’s friendship group (hypothetically) approves of such discriminatory behaviour, the likelihood of acting in a politically violent manner is increased, even for adolescents who do not support group-focused enmity.